Menegakkan Etika Hukum di Era Digital: Kolaborasi Teknologi, Regulasi, dan Masyarakat dalam Pemberantasan Korupsi - Fadly Surya Wijaya; Agus riyadi; Rifqy Afrizal Siddik; Mochammad ridzky salatun; Witandri; Firman Adi Candra (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
This article examines the strategic role of information technology in strengthening legal ethics enforcement amid Indonesia’s ongoing efforts to combat corruption. In the digital era, addressing corruption can no longer rely solely on repressive legal mechanisms but requires a transparent, accountable, and participatory system. Using a normative-qualitative approach, this study explores how digital innovations such as e-procurement, whistleblowing systems, the JAGA platform developed by the Corruption Eradication Commission (KPK), and blockchain technology have become crucial tools in promoting openness and public accountability. However, the effectiveness of these technologies depends greatly on adaptive regulations and active public engagement. Collaboration between legal frameworks, technological systems, and a culture of civic reporting forms the foundation for a more robust and responsive legal ethics system. The article concludes that the success of legal ethics enforcement in the digital age can only be achieved through continuous synergy between innovation, regulation, and citizen participation.